Current level of infective endocarditis prevention awareness among dentists and patients with artificial valves - Pawlus, Bartłomiej; Markowicz-Pawlus, Ewa; Špidlen, Miloš (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Background : For many years, the prophylactic use of antibiotics in patients with heart diseases associated with a high risk of infective endocarditis (IE) was a common practice. In patients with artificial valves, the morbidity and mortality in the occurrence of IE reaches several dozen percent. Currently, the only treatments that require IE prophylaxis are dental procedures. Aim of the study : The aim of this study was to assess IE prevention awareness among dentists and patients with artificial valves. Material and methods : We analyzed 48 patients (26 men and 22 women) after artificial valve implantation. The time since their surgery was 4.5 ±1.5 years. Twenty-nine patients (67.4%) had an artificial aortic valve, 19 (39.6%) had a mitral valve. Mean age was 67.5 ±6.2 years. Information on IE prophylaxis was obtained during routine outpatient visits. Questionnaires concerning IE prophylaxis were distributed among 35 dentists. Results: Forty-one patients (85.4%) were aware of the need for IE prophylaxis, of whom 28 (68.2%) identified only dental procedures as requiring IE prevention, while 14 patients (34.1%) included gastroscopy, colonoscopy, and coronarography in this category, and 18 patients (43.9%) identified amoxicillin as the recommended antibiotic. Fifty-four (98.2%) dentists indicated that patients with artificial valves require IE prophylaxis, while 41/55 (74.5%) indicated amoxicillin or ampicillin as the recommended prophylactic agent. All the dentists saw the need for IE prophylaxis before tooth extraction; 50 (90.9%) – during root canal treatment; 50 (90.9%) – during procedures around the gingiva. 10 respondents (18.2%) did not recommend IE prophylaxis before tooth implantation; 10 (18.2%) – before removing tartar. Conclusions: The large majority of patients with artificial heart valves are aware of the need for IE prevention. The knowledge of dentists concerning IE prophylaxis requires verification in accordance with the current guidelines.